Efficient removal of nanoplastics from industrial wastewater through synergetic electrophoretic deposition and particle-stabilized foam formation - Abdeljaoued, Amna; Ruiz, Beatriz López; Tecle, Yikalo Eyob; Langner, Marie; Bonakdar, Natalie; Bleyer, Gudrun; Stenner, Patrik; Vogel, Nicolas (Nature Communications, 2024)
Microplastic particles have been discovered in virtually all ecosystems worldwide, yet they may only represent the surface of a much larger issue. Nanoplastics, with dimensions well below 1 µm, pose an even greater environmental concern. Due to their size, they can infiltrate and disrupt individual cells within organisms, potentially exacerbating ecological impacts. Moreover, their minute dimensions present several hurdles for removal, setting them apart from microplastics. Here, we describe a process to remove colloidally stable nanoplastics from wastewater, which synergistically combines electrophoretic deposition and the formation of particle-stabilized foam. This approach capitalizes on localized changes in particle hydrophilicity induced by pH fluctuations resulting from water electrolysis at the electrode surface. By leveraging these pH shifts to enhance particle attachment to nascent bubbles proximal to the electrode, separation of colloidal particles from aqueous dispersions is achieved. Using poly(methyl methacrylate) (PMMA) colloidal particles as a model, we gain insights into the separation mechanisms, which are subsequently applied to alternative model systems with varying surface properties and materials, as well as to real-world industrial wastewaters from dispersion paints and PMMA fabrication processes. Our investigations demonstrate removal efficiencies surpassing 90%.
CRIS-Team Scopus Importer:2024-07-12

Inverse opals with reactive surface chemistry as sensors for aqueous pollutants - Magnabosco, Giulia; Ochs, Maria; Bonakdar, Natalie; Czerwenka, Laura; Andrieu-Brunsen, Annette; Vogel, Nicolas (Chemical Communications, 2024)
Inverse opal colorimetric sensors operating on wetting transitions usually rely on physical differences of the infiltrating liquid. Here, we exploit a reactive surface chemistry that changes wettability upon binding of an analyte. Upon binding of Fe3+ to a Schiff base immobilized on the porous structure, the surface becomes more hydrophilic, triggering the infiltration of the structure and causing the structural color to disappear.
CRIS-Team Scopus Importer:2024-07-12

Recycling the recyclers: strategies for the immobilisation of a PET-degrading cutinase - Fritzsche, Stefanie; Popp, Marcus; Spälter, Lucas; Bonakdar, Natalie; Vogel, Nicolas; Castiglione, Kathrin (Bioprocess and Biosystems Engineering, 2025)
Enzymatic degradation of polyethylene terephthalate (PET) represents a sustainable approach to reducing plastic waste and protecting fossil resources. The cost efficiency of enzymatic PET degradation processes could be substantially improved by reusing the enzymes. However, conventional immobilisation strategies, such as binding to porous carriers, are challenging as the immobilised enzyme can only interact with the macromolecular solid PET substrate to a limited extent, thus reducing the degradation efficiency. To mitigate this challenge, this work compared different immobilisation strategies of the PET-degrading cutinase ICCGDAQI. Immobilisation approaches included enzyme fixation via linkers to carriers, the synthesis of cross-linked enzyme aggregates with different porosities, and immobilisation on stimulus-responsive polymers. The highest degradation efficiencies were obtained with the pH-responsive material Kollicoat®, where 80% of the initial enzyme activity could be recovered after immobilisation. Degradation of textile PET fibres by the cutinase-Kollicoat® immobilisate was investigated in batch reactions on a 1 L-scale. In three consecutive reaction cycles, the product yield of the released terephthalic acid exceeded 97% in less than 14 h. Even in the fifth cycle, 78% of the maximum yield was achieved in the same reaction time. An advantage of this process is the efficient pH-dependent recovery of the immobilisate after the reaction, which integrates seamlessly into the terephthalic acid recovery by lowering the pH after hydrolysis. This integration therefore not only simplifies the downstream processing, but also provides a cost-effective and resource-efficient solution for both enzyme reuse and product separation after PET degradation, making it a promising approach for industrial application.
CRIS-Team Scopus Importer:2025-02-14
Keywords: Cross-linked enzyme aggregates; Enzymatic depolymerisation; Kollicoat; Plastic waste; Polyethylene terephthalate; Stimulus-responsive polymers